STUDYING THE POSSIBILITY OF REDUCING THE PERIOD OF SEED DORMANCY IN CROPS UNDER CONTROLLED GROWTH CONDITIONS - Khlebova, L. P.; Arzumanyan, A. A. (Acta Biologica Sibirica, 2015)
The effect of growth temperature on the seed properties and grain quality of the crops was studied. It found that the increasing temperature leads to decrease of sizes and increase of the protein content in grain of spring wheat. It was determined that a reduction in the period of seed dormancy in spring oats and durum wheat under the influence of high temperature during ripening enhances germination energy and seed germination. In wheat high temperature reduces these figures when sowing seeds freshly harvested.